Global response of conservationists across mass media likely constrained bat persecution due to COVID-19. (August 2022) - Nanni, Veronica; Mammola, Stefano; Macías-Hernández, Nuria; Castrogiovanni, Alessia; Salgado, Ana L.; Lunghi, Enrico; Ficetola, Gentile Francesco; Modica, Corrado; Alba, Riccardo; Spiriti, Maria Michela; Holtze, Susanne; de Mello, Érica Munhoz; et al.
Abstract: Most people lack direct experience with wildlife and form their risk perception primarily on information provided by the media. The way the media frames news may substantially shape public risk perception, promoting or discouraging public tolerance towards wildlife. At the onset of the COVID-19 pandemic, bats were suggested as the most plausible reservoir of the virus, and this became a recurrent topic in media reports, potentially strengthening a negative view of this ecologically important group. We investigated how media framed bats and bat-associated diseases before and during the COVID-19 pandemic by assessing the content of 2651 online reports published across 26 countries, to understand how and how quickly worldwide media may have affected the perception of bats. We show that the overabundance of poorly contextualized reports on bat-associated diseases likely increased the persecution towards bats immediately after the COVID-19 outbreak. However, the subsequent interventions of different conservation communication initiatives allowed pro-conservation messages to resonate across the global media, likely stemming an increase in bat persecution. Our results highlight the modus operandi of the global media regarding topical biodiversity issues, which has broad implications for species conservation. Knowing how the media acts is pivotal for anticipating the propagation of (mis)information and negative feelings towards wildlife. Working together with journalists by engaging in dialogue and exchanging experiences should be central in future conservation management. Highlights: COVID-19 increased bats persecution at the beginning of the pandemic Communication strategies for wildlife conservation should involve mass media Attractive topics spread rapidly across the globe in the media Conservationists should react promptly to negative media content, especially when their online spread accelerates